2020
DOI: 10.26452/ijrps.v11i2.2239
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacological, bioactive screening of medicinal plant Nigella sativa and the derived compound thymoquinone : An invitro study

Abstract: The richest biosource of drugs are from the medicinal plants which are the traditional medicine. The nutraceuticals, food supplements, Siddha, Ayurveda, pharamceutical medicines, synthetic drugs are from the plant sources. Inspite of large number of studies with herbal plants which have given good correlation in the phytochemical, anti-diabetic and anti-inflammatory content, Nigella sativa- a spice plant of Ranunculacea family showed significant properties than their counterparts. The seeds of Nigella sativa a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
1

Year Published

2021
2021
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 12 publications
0
2
1
Order By: Relevance
“…Compared to our findings, it was reported in Value et al's [25] study that the aqueous extract was able to inhibit the α-amylase in a dose-dependent manner, and an inhibition capacity of about 84% at a dose of 100 mg/ml was observed, although, in our work, we found that it inhibits the enzyme with a percentage of 91.49% at a dose of 1.82 mg/ml. Our EtOH fractions gave an IC 50 value of about 250 μg/ml that was higher than that obtained in Sandhya and Kannayiram's [26] study, and it was equal to 100 μg/ml. In Buchholz and Melzig's study [27], an inhibition percentage of 45% at a concentration of 2.5 mg/ml was registered which was less effective than that obtained in our results where the IC 50 value was 100 μg/ml.…”
Section: Discussioncontrasting
confidence: 76%
“…Compared to our findings, it was reported in Value et al's [25] study that the aqueous extract was able to inhibit the α-amylase in a dose-dependent manner, and an inhibition capacity of about 84% at a dose of 100 mg/ml was observed, although, in our work, we found that it inhibits the enzyme with a percentage of 91.49% at a dose of 1.82 mg/ml. Our EtOH fractions gave an IC 50 value of about 250 μg/ml that was higher than that obtained in Sandhya and Kannayiram's [26] study, and it was equal to 100 μg/ml. In Buchholz and Melzig's study [27], an inhibition percentage of 45% at a concentration of 2.5 mg/ml was registered which was less effective than that obtained in our results where the IC 50 value was 100 μg/ml.…”
Section: Discussioncontrasting
confidence: 76%
“…It could be inferred that Gedunin restored the activity of all the enzymes by inhibiting ROS production. The results are in agreement with other studies where the phytoactives restored enzyme activity [ 36 , 37 ]. The restoration of GSH may be a consequence of increased activity of GRD revitalized by Gedunin.…”
Section: Discussionmentioning
confidence: 99%
“…It is obvious that N. sativa seeds could meet the nutritional need to improve the immune system of an organism (30). Research on the chemical constituents of this genus began in the middle of the 20th century (31), which showed that N. sativa seeds contain various chemical components like essential oils, alkaloids, phenols, saponins, and steroids (32,33).…”
Section: Introductionmentioning
confidence: 99%